Current best practice in the management of neuroendocrine tumors. (January 2019) - Tsoli, Marina; Chatzellis, Eleftherios; Koumarianou, Anna; Kolomodi, Dionysia; Kaltsas, Gregory
Neuroendocrine neoplasms are rare tumors that display marked heterogeneity with varying natural history, biological behavior, response to therapy and prognosis. Their management is complex, particularly as a number of them may be associated with a secretory syndrome and involve a variety of options. A number of factors such as proliferation rate, degree of differentiation, functionality and extent of the disease are mostly utilized to tailor treatment accordingly, ideally in the context of a multidisciplinary team. In addition, a number of relevant scientific societies have published therapeutic guidelines in an attempt to direct and promote evidence-based treatment. Surgery remains the treatment of choice with an intention to cure while it may also be recommended in some cases of metastatic disease and difficult to control secretory syndromes. Long-acting somatostatin analogs constitute the main treatment for the majority of functioning tumors, whereas specific evolving agents such as telotristat may be used for the control of carcinoid syndrome and related sequelae. In patients with advanced disease not amenable to surgical resection, treatment options include locoregional therapies, long-acting somatostatin analogs, molecular targeted agents, radionuclides, chemotherapy and recently immunotherapy, alone or in combination. However, the ideal time of treatment initiation, sequence of administration of different therapies and identification of robust prognostic markers to select the most appropriate treatment for each individual patient still need to be defined.